Study and analysis of the reasons for the lack of competitiveness of portuguese construction industry : implemented research surveys - Couto, J. Pedro (2006)
The lack of accomplishment of the main management functions in construction projects had been reported worldwide. The symptoms are well recognized, like cost and time overruns, defícient quality and lack of safety. To help clarifying the reasons for this evidence, several surveys were carried to Portuguese construction stakeholders by a team research of construction management of University of Minho. The PhD survey results to confirm the original list of causes for delays of the study namely poor productivity, procurement system, and frequent change orders during construction and so on. In order to correct the above problems and improve construction competitiveness should be implemented a national database with the quantity works list for different construction projects, a more appropriate and efficient organizational systems within design teams and a need for greater care on the part of the owners when they prepare their schedules and preliminary programs. On the other hand, it was clear that despite the apparent advantages of Internet survey approach, traditional methods like fax, phone calls and interviews appear to be most successful and still are preferred by respondents.